Reflective learning model in moral education: The relevance of K.H. Hasyim Asy'ari’s thoughts in the modern era - Nasrowi, Bagas Mukti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Moral education constitutes the core of holistic human character development, encompassing not only cognitive dimensions but also affective and spiritual aspects. In the Islamic educational framework, morality holds a central position as it reflects the true success of knowledge transmission. Amid the current moral crisis affecting younger generations—fueled by the rapid flow of information and technological advancement—moral education must be redirected toward fostering moral awareness through a reflective learning approach. This article explores the relevance of reflective learning in light of the thoughts of Hadratussyaikh K.H. Hasyim Asy'ari as presented in his seminal work Adāb al-ʻĀlim wa al-Mutaʻallim. Employing a qualitative method with a biographical approach and literature-based research, data were collected through documentation. Data analysis followed Creswell’s six-step process: organizing data, reading, coding, developing themes, presenting findings, and interpreting results. The study reveals that both students and teachers must cultivate proper ethical conduct (adab) toward themselves as a foundational aspect of moral education. This adab aligns with reflective learning principles, emphasizing self-evaluation (muhasabah), exemplary behavior, and inner awareness. Integrating reflective approaches with classical Islamic values offers a contextual and applicable model for moral education in the modern era.